DEGRADATION KINETICS OF TEXTILE AZO DYE REACTIVE ORANGE-16 BY GAMMA IRRADIATION (Jurnal Teknologi (Sciences & Engineering), 2024)
Gamma radiation have become attention since their high potential for degrading compounds, especially organic pollutants. In this research, gamma radiation was studied for degrading the Reactive Orange-16 (RO-16) dye, a toxic and carcinogenic pollutant. The radiolytic degradation process was studied in a batch reactor with a gamma-ray dose rate of 2.930 kGy/h. The effect of experimental variable such as initial peroxide concentration, initial pH, initial dye concentration, and addition of inorganic anion were studied. The highest degradation rates were achieved at a peroxide concentration ranging from 2 to 4 mM. In contrast, the higher peroxide concentration indicated the slower degradation process caused by the scavenging effect of the peroxide. Degradation of 88% RO-16 dye with 0.1 mM initial concentration, was achieved at 2.0 kGy irradiation dose and 97.4% degradation in the presence of 4 mM peroxide. The dose constant (d) for those degradation processes was 1.0657 kGy-1 and 1.8420 kGy-1 respectively. The degradation was more efficient in acid pH. The degradation process increased with lower initial dye concentrations. The degradation of RO-16 dye by gamma-ray was inhibited by the presence of inorganic anions in the following sequence: NO3-→ CO32− → HCO3− → CH3COO-→ Cl-.